2022
DOI: 10.1017/jfm.2022.674
|View full text |Cite
|
Sign up to set email alerts
|

On coherent vortical structures in wave breaking

Abstract: The flow generated by the breaking of free-surface waves in a periodic domain is simulated numerically with a gas–liquid Navier–Stokes solver. The solver relies on the volume-of-fluid method to account for different phases, and the interface tracking is carried out by using novel schemes based on a tailored total-variation-diminishing limiter. The numerical solver is proved to be characterized by a low numerical dissipation, thanks to the use of a scheme that guarantees energy conservation in the discrete form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 103 publications
(188 reference statements)
4
6
0
Order By: Relevance
“…We note that for equivalent diameters above the Hinze scale, our results follow quite well the theoretical scaling law and match the size distributions of the drops/bubbles obtained in the literature considering similar flow instances (Deike, Melville & Popinet 2016; Soligo, Roccon & Soldati 2021; Deike 2022; Di Giorgio, Pirozzoli & Iafrati 2022; Crialesi-Esposito, Chibbaro & Brandt 2023). Below the Hinze scale, for equivalent diameters in the range , our results match reasonably well the theoretical scaling law.…”
Section: Resultssupporting
confidence: 88%
“…We note that for equivalent diameters above the Hinze scale, our results follow quite well the theoretical scaling law and match the size distributions of the drops/bubbles obtained in the literature considering similar flow instances (Deike, Melville & Popinet 2016; Soligo, Roccon & Soldati 2021; Deike 2022; Di Giorgio, Pirozzoli & Iafrati 2022; Crialesi-Esposito, Chibbaro & Brandt 2023). Below the Hinze scale, for equivalent diameters in the range , our results match reasonably well the theoretical scaling law.…”
Section: Resultssupporting
confidence: 88%
“…Deane, Stokes & Callaghan (2016) discussed turbulence saturation, where the increase in plume cross-sectional area is more relevant than the increase in fluid shear stress within the plume. Giorgio, Pirozzoli & Iafrati (2022) corroborated the findings that the dissipated energy fraction does not depend much on the Reynolds number or dimensionality. Mostert, Popinet & Deike (2022) observed that the Reynolds number does not affect the shape of the bubble size distribution after Re reaches a threshold, as the mean turbulent dissipation rate is not sensitive to Re.…”
Section: Assessment Of Low-reynolds-number Dns For Insights Into Vent...supporting
confidence: 83%
“…(2016), Giorgio et al. (2022) and Mostert et al. (2022), the mean volume fraction of air, the mean velocity, and the pressure distributions inside the cavity obtained in the present study may help the understanding of the underlying dynamics of these flow processes.…”
Section: Assessment Of Low-reynolds-number Dns For Insights Into Vent...supporting
confidence: 65%
See 1 more Smart Citation
“…Describing breaking waves analytically and numerically has been challenging due to their nonlinear nature and the fact that the interface becomes multi-valued. Considering a single breaker, scaling analyses have been successfully proposed for energy dissipation, validated by laboratory experiments (Drazen, Melville & Lenain 2008;Perlin, Choi & Tian 2013); and, thanks to advances in numerical methods and increasing computational power, high fidelity simulations of single three-dimensional (3-D) breakers have emerged (Wang, Yang & Stern 2016;Deike, Melville & Popinet 2016;Gao, Deane & Shen 2021;Di Giorgio, Pirozzoli & Iafrati 2022;Mostert, Popinet & Deike 2022). Other approaches to incorporating breaking wave fields into intermediate-scale modelling include work based on Reynolds averaged Navier Stokes equations and large eddy simulation modelling (Larsen & Fuhrman (2018) and Derakhti et al (2016) among others), but are restricted to individual breaking events or prescribe the breaking statistics instead of resolving it (Sullivan, McWilliams & Melville 2004, 2007.…”
Section: Introductionmentioning
confidence: 99%